When is a Bill of Rights Fit for Judicial Review? The Limitation of Rights Regime in the Netherlands Considered - Gerhard van der Schyff (Utrecht Law Review, 2013)
Justifying the judicial application of fundamental rights is forever a fiercely debated topic. Equally important, but often less studied, is the question of whether the formulation of rights, and in particular the limitation regime applicable to rights, conduct or aid the proper review of such provisions. As the Netherlands debates whether to allow a constitutional review of (some) fundamental rights the question arises as to the suitability of its limitation regime. This question is addressed by reference to general limitation theory. In particular attention will be paid to the notion of what constitutes a limit in constitutional theory in order for two limitation models (a one-stage and a two-stage model) to be developed. The models will then be applied to the situation under the Constitution of the Netherlands, as well as to recent reform proposals by the State Commission on Constitutional Reform. The contribution concludes with some general thoughts on the function of limitation provisions.